Market Reactions to Religious National Holidays: Evidence from Idul Fitri and Idul Adha in Consumer Cyclical Firms Listed on the Indonesia Stock Exchange - Hassan, Khothibul Umam; Prasetyo, Tri Joko (Universitas Mercu Buana, 2025)
This study examines the impact of Islamic religious holidays Eid al-Fitr and Eid al-Adha on the Indonesian capital market, focusing on abnormal returns (AR) and trading volume activity (TVA) in the consumer cyclicals sector. Using an event study methodology, data from 70 companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 were analyzed. The results indicate a significant market reaction to Eid al-Fitr, with abnormal returns observed on H−3 (three days before) and H+2 (two days after the event, suggesting investor anticipation of increased consumer spending. However, no significant AR or TVA anomalies were detected for Eid al-Adha, likely due to its lesser economic impact. Trading volumes showed no statistically significant changes during either holiday, aligning with the semi-strong form of the Efficient Market Hypothesis (EMH), which posits that public information is rapidly reflected in stock prices. These findings highlight the nuanced influence of cultural and religious events on market behavior, with Eid al-Fitr generating short-term inefficiencies while Eid al-Adha does not. The study contributes to the literature on behavioral finance and market efficiency in emerging economies, offering insights for investors and policymakers on holiday-driven market dynamics.